How do patients with end-stage ankle arthritis decide between two surgical treatments? A qualitative study. Issue 7 (16th July 2013) - Zaidi, Razi; Pfeil, Michael; Macgregor, Alexander J; Goldberg, Andy
Abstract : Objective: To examine how patients decide between ankle fusion and ankle replacement in end-stage ankle arthritis. Design: Purposive patient selection, semistructured interviews, thematic analysis. Setting: Royal National Orthopaedic Hospital, Stanmore, UK. Participants: 14 patients diagnosed with end-stage ankle osteoarthritis. Results: We interviewed 6 men and 8 women with a mean age of 58 years (range 41–83). All had opted for surgery after failure of at least 6 months of conservative management, sequentially trading-off daily activities to limit the evolving pain. To decide between two offered treatments of ankle fusion and total ankle replacement (TAR), three major sources informed the patients' decision-making process: their surgeon, peers and the internet. The treating surgeon was viewed as the most reliable and influential source of information. Information gleaned from other patients was also important, but with questionable reliability, as was information from the internet, both of which invariably required validation by the surgeon and in some cases the general practitioner. Conclusions: Patients seek knowledge from a wealth of sources including the internet, web forums and other patients. While they leverage each of these sources to guide decision-making, the most important and influential factor in governing how patients decide on any particular surgical intervention is their surgeon. A high quality doctor–patient relationship, coupled with clear, balanced and complete information is essential to enable shared decision-making to become a standard model of care.